2010
DOI: 10.1111/j.1532-5415.2010.02764.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and 10‐Year Outcomes of Frailty in Older Adults in Relation to Deficit Accumulation

Abstract: OBJECTIVES:To evaluate the prevalence and 10-year outcomes of frailty in older adults in relation to deficit accumulation. DESIGN: Prospective cohort study. SETTING: The National Population Health Survey of Canada, with frailty estimated at baseline (1994/95) and mortality follow-up to 2004/05. PARTICIPANTS: Community-dwelling older adults (N 5 2,740, 60.8% women) aged 65 to 102 from 10 Canadian provinces. During the 10-year follow-up, 1,208 died. MEASUREMENTS: Self-reported health information was used to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
649
7
27

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 888 publications
(723 citation statements)
references
References 39 publications
40
649
7
27
Order By: Relevance
“…Regarding mortality, our results are consistent with previous studies showing that at all ages, a higher FI was associated with higher mortality [13,24], and that the FI predicts death better than chronological age [22]. In the Chinese Longitudinal Healthy Longevity Survey, the FI was a robust predictor of mortality at advanced ages and the relationship between frailty and mortality was independent of age and other covariates [25].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding mortality, our results are consistent with previous studies showing that at all ages, a higher FI was associated with higher mortality [13,24], and that the FI predicts death better than chronological age [22]. In the Chinese Longitudinal Healthy Longevity Survey, the FI was a robust predictor of mortality at advanced ages and the relationship between frailty and mortality was independent of age and other covariates [25].…”
Section: Discussionsupporting
confidence: 90%
“…Thirty-nine variables had the recommended <5% of missing data [13]. Grip strength had 10.1% of missing data, but it was retained as it is known to be an important objective marker of frailty [14,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important predictor of disability, institutionalization and death, [1][2][3][4][5][6][7][8][9][10] old age frailty will rise to a public health issue of remarkable proportions during the coming decades. Although no strict consensus criteria have been established to date, 2,7 the phenotypic criteria described by Fried et al 1 are commonly used to define frailty as a geriatric syndrome characterized by excess vulnerability, loss of resiliency and multi-system decline.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown that more manageable 30 parameters of FI model [45], simpler models with minimal overlap in identification [46] or existing electronic health record data can have competitive predictive validity [44].…”
Section: Frailtymentioning
confidence: 99%